Umm Salamah's Compassion: Bridging Orphan Welfare From Battlefield To Modern Law - Binte Mahfuh, Siti Khadijah; Ariffin, Tajul; Kosasih, Engkos (TAQNIN: Jurnal Syariah dan Hukum, 2024)
This article, titled "Umm Salamah's Compassion: Bridging Orphan Welfare from Battlefield to Modern Law," examines the life and influence of Umm Salamah, a pivotal figure in early Islamic scholarship known for her courage and compassion. Through a qualitative analysis of her contributions to Hadith scholarship, this study explores how historical Islamic practices can inform contemporary legal frameworks. Specifically, it addresses the deficiencies in Singapore's laws on orphan protection and welfare, proposing that Umm Salamah's principles offer valuable insights to improve modern legal systems. The methodology framework behind this study is sociological and normative, as it examines her enduring influence, illuminating her legacy as a trailblazer in Islamic scholarship. The study integrates the concept of Maqashid Sharia (objectives of Islamic law), particularly in relation to social justice and the welfare of orphans. Her contributions enriched Islamic thought and how Umm Salamah's work aligns with the principles of Maqashid Sharia, emphasizing the protection and welfare of vulnerable groups.